5e+7=17

Simple and best practice solution for 5e+7=17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5e+7=17 equation:


Simplifying
5e + 7 = 17

Reorder the terms:
7 + 5e = 17

Solving
7 + 5e = 17

Solving for variable 'e'.

Move all terms containing e to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 5e = 17 + -7

Combine like terms: 7 + -7 = 0
0 + 5e = 17 + -7
5e = 17 + -7

Combine like terms: 17 + -7 = 10
5e = 10

Divide each side by '5'.
e = 2

Simplifying
e = 2

See similar equations:

| 53-4x=29-3x | | 35-3x=14-10x | | 3x-24=4x-8 | | 1-3x(1)-(-3)-2(x-3)=3x-(-4) | | 2x+7=6x+19 | | (8x-64x^(-1/2)) | | -(8v-7)=25-5v | | -7f=56 | | (7x+1)(8x-6)= | | x+7=3x+9.5 | | (x^(2/3)y^(-(5/4)))^6 | | 1.4/7.7 | | lg(x^2-x-6)-lg(x-3)=0 | | 25x^2+35x=0 | | 5=-7+a | | 40=-8(x+2) | | 1.5y-2=y | | 1/2x+2/5=1/3x+3/4 | | 10*t+6*(0.8-t)=6 | | (x-16)2=64 | | 9x+20=2x+125 | | 4x-6=x-18 | | -5k-2+9k+6= | | 1/2(6x-4)-4x=3x-18 | | x^4+18x^2+17=0 | | 3x-x+1=2x+5 | | 7=n+5 | | x*x+25=10x | | 9n+7n-5-4= | | 4x-5y+3z= | | .75(4-8x)=0.8(5+10x)+1 | | a(3a-2)+2a(a+4)=a(a+2) |

Equations solver categories